2016
DOI: 10.2464/jilm.66.266
|View full text |Cite
|
Sign up to set email alerts
|

Stress corrosion cracking and corrosion resistance of Mg–6%Al–1%Zn–2%Ca extruded magnesium alloys

Abstract: Stress corrosion cracking (SCC) and corrosion resistance of Mg-6 mass%Al-1 mass%Zn-1 mass%Ca (AZX612) extruded alloy were investigated by slow strain rate tensile tests (SSRT) in 0.01 M NaCl solution and immersion tests in 5 mass% NaCl solution, and compared with those of Mg-6 mass%-1 mass%Zn (AZ61) extruded alloy. In the SSRT in the salt solution, as-received AZX612 exhibited lower elongation and higher SCC susceptibility than those of as-received AZ61, indicating that calcium addition in Mg-Al alloy deterior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 22 publications
1
1
0
Order By: Relevance
“…Figure 1 shows the XRD and XPS results of the surface of the AZX612 before and after the anodic oxidization. Refering to the reports by Serizawa et al 18) and Yuasa et al, 19) peaks of Mg, Al 2 Ca, Mg 17 Al 12 , and AlMn compounds were observed in the both XRD patterns. It is considered that the unmarked peaks, which were not observed in the above references, were derived from some compounds generated by the manufacturing process of the untreated substrate.…”
Section: Resultssupporting
confidence: 68%
“…Figure 1 shows the XRD and XPS results of the surface of the AZX612 before and after the anodic oxidization. Refering to the reports by Serizawa et al 18) and Yuasa et al, 19) peaks of Mg, Al 2 Ca, Mg 17 Al 12 , and AlMn compounds were observed in the both XRD patterns. It is considered that the unmarked peaks, which were not observed in the above references, were derived from some compounds generated by the manufacturing process of the untreated substrate.…”
Section: Resultssupporting
confidence: 68%
“…They were identified as Al 2 Ca using XRD. 21 The volume fraction increased with an increase in the Ca content.…”
Section: Resultsmentioning
confidence: 95%